Rancang Bangun Sistem Monitoring dan Dokumentasi Permasalahan Kebersihan dan Kenyamanan Penumpang Berbasis Web di Stasiun Kereta Api - Ali Ikhwan; Muhammad Rayhan; Bagus Susanto (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Cleanliness and passenger comfort significantly affect service quality at railway stations. Currently,x` cleanliness management relies heavily on verbal instructions and manual reporting methods, resulting in inefficiencies in monitoring and documentation. This research aims to digitize reporting, monitoring, and documentation processes through a web-based system. The system was developed using the Software Development Life Cycle (SDLC) methodology, which includes planning, analysis, design, implementation, and testing phases. Two main user roles are involved: Facility and Station Security (Kebfasta and Kebfaska) division officers as report initiators, and cleaning staff (OSC/K2) as task responders. Reports and task completions are digitally documented, enabling real-time monitoring, effective documentation, and automated generation of daily or monthly reports. Evaluation results demonstrate that this implemented system significantly improves documentation accuracy, reduces response time, and enhances the management of cleanliness and passenger comfort in railway stations.